Farmers’perception of veterinary services in Bangladesh (Bangladesh Veterinarian, 2023)
Farmers’ perception of veterinary services at the Upazila (Sub-district) Veterinary Hospital (UVH), and constraints of livestock farming in Bangladesh were studied. Data from 135 livestock farmers which were obtained, using a pretested questionnaire. Most of the farmers (99.3%) had small families. Most were illiterate (60.0%), 22.2% had Secondary School Certificate and 17% had Higher Secondary Certificate or above. Mostly, stall feeding system was practised (76.9%), concentrated feed (71.9%) and water (68.9%) were supplied twice daily and animals were dewormed at regular intervals (51.1%). Irregular vaccinations were followed by 15.6% farmers. Only 55.2% of farmers called on veterinary surgeons when their animals were sick. About 77.6% farmers were satisfied with the existing public veterinary services.About 32.1% farmers got veterinary services at their door step by the veterinary surgeons whereas 29.9, 28.4 and 8.2% farmers received drugs, services, and free vaccination, respectively. Poor knowledge of farming (71.3%), feeds and fodder scarcity (55.6%) and unavailability of safe water (64.4%) were the main constraints identified. It is suggested that more training and veterinary extension programmes for farmers are required.Bangl. vet. 2022. Vol. 39, No. 1-2, 26–33